Cognitive function and stress as determinants of independence among older adults in institutional care: A cross-sectional study - Nailah, Intan Hana; Akhmad Faozi; Delli Yuliana Rahmat (Lentera Perawat, 2025)
Background: The global increase in the older adult population is accompanied by complex health challenges, including cognitive decline, elevated stress levels, and decreased independence in activities of daily living. In Indonesia, approximately 12.7% of older adults experience dependency in basic activities, influenced by factors such as chronic disease, depression, low physical activity, limited social support, and cognitive impairment, which collectively accelerate functional decline. Objective: This study aimed to examine the relationship between cognitive function and stress levels with independence among older adults residing at Griya Lansia Ciparay. Methods: A quantitative study with a cross-sectional design was conducted involving 61 older adults selected through purposive sampling based on predefined inclusion criteria. Cognitive function was assessed using the Mini-Mental State Examination (MMSE), stress levels were measured with the Perceived Stress Scale (PSS-10), and independence was evaluated using the Barthel Index. Data were analyzed using univariate analysis to describe variable distributions and bivariate analysis employing the Spearman Rho correlation test. Results: The findings revealed a statistically significant relationship between cognitive function and stress levels with independence among older adults (p = 0.001). Older adults with better cognitive function and lower stress levels demonstrated higher levels of independence in performing daily activities. Conclusion: Cognitive function and stress levels are significantly associated with independence among older adults. Strategies aimed at preserving cognitive abilities and managing psychological stress are essential to maintain functional independence and improve quality of life in the elderly population, particularly in institutional care settings.